Safety and efficiency of stem cell therapy for COVID-19: a systematic review and meta-analysis - Minghe Zhang; Xinchun Yan; Minghui Shi; Ruihang Li; Ziwei Pi; Xiangying Ren; Yongbo Wang; Siyu Yan; Yunyun Wang; Yinghui Jin; Xinghuan Wang (BMC, 2022)
Abstract Background With the COVID-19 pandemic continuing, various treatments have become widely practiced. Stem cells have a wide range of applications in the treatment of lung diseases and have therefore been experimentally used to treat patients with COVID-19, but whether the expanded use of stem cells is safe and reliable still lacks enough evidence. To address this issue, we systematically reviewed the safety and efficiency of stem cell therapy in COVID-19 cases. Methods We searched PubMed, Embase, Web of Science, The Cochrane Library, CNKI, WanFang, VIP and SinoMed up to January 18, 2022. The included studies were assessed using the Risk-of-bias tool 1.0 and MINORS instrument. The adverse events, mortality, length of hospital day and laboratory parameters were analyzed by meta-analysis. We adhered to PRISMA reporting guideline. Results We have included 17 studies meeting the inclusion data. There were no significant differences in AEs (OR = 0·39, 95% CI = 0·12 to 1·33, P = 0·13, I2 = 58%) and SAEs (OR = 0·21, 95% CI = 0·04 to 1·03, P = 0·05, I2 = 0%) between stem cell therapy group and control group. The analysis showed that stem cell treatment could significantly reduce the mortality rate(OR = 0·24, 95% CI = 0·13 to 0·45, P < 0·01, I2 = 0%), but was not able to cause changes in length of hospital stay or most laboratory parameters. Conclusions The present study shows that stem cell therapy for COVID-19 has a remarkable effect on efficiency without increasing risks of adverse events and length of hospital stay. It is potentially necessary to establish the criteria for COVID-19 for stem cell therapy.